2021
DOI: 10.3390/molecules26010206
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome and Its Implications in Cancer Immunotherapy

Abstract: Cancer is responsible for ~18 million deaths globally each year, representing a major cause of death. Several types of therapy strategies such as radiotherapy, chemotherapy and more recently immunotherapy, have been implemented in treating various types of cancer. Microbes have recently been found to be both directly and indirectly involved in cancer progression and regulation, and studies have provided novel and clear insights into the microbiome-mediated emergence of cancers. Scientists around the globe are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 265 publications
0
9
0
Order By: Relevance
“…The principle of immunotherapy is based on the fundamental concept, 'cancer immunoediting', stating that the immune system can be protective to the host meanwhile prompting cancer progression. 17 During immunoediting, the immune system shapes the immunogenicity of tumours in three phases-elimination, equilibrium and escape. 17 In the first phase, both innate and adaptive immune systems detect and destroy early tumours before they become clinically visible.…”
Section: Antitumour Immunity and Tumour Microenvironmentmentioning
confidence: 99%
“…The principle of immunotherapy is based on the fundamental concept, 'cancer immunoediting', stating that the immune system can be protective to the host meanwhile prompting cancer progression. 17 During immunoediting, the immune system shapes the immunogenicity of tumours in three phases-elimination, equilibrium and escape. 17 In the first phase, both innate and adaptive immune systems detect and destroy early tumours before they become clinically visible.…”
Section: Antitumour Immunity and Tumour Microenvironmentmentioning
confidence: 99%
“…This phenomenon is further reflected by the observation that the gut microbiome of patients with CRC displays prominent differences compared with healthy individuals, including reduced butyrate-producing bacterial lineages and enriched levels of pathogenic bacteria such as Escherichia coli, Salmonella and Shigella. Such bacteria have been shown to strongly adhere to colonic epithelial cells and induce DNA damage in vitro (rat cell lines) and in vivo (CRC mouse models) 3,[241][242][243] . Patients with CRC also display an altered virome (such as presence of cytomegalovirus) and mycobiome (for example, abundance of fungal Malassezia), when compared with healthy individuals, but no link with neural messengers has been established yet 228 .…”
Section: Neural Signals and Innate Immune Cellsmentioning
confidence: 99%
“…Many factors are deciding the immunotherapy efficacy, including mutational load, cancer metabolism, and microbiota [ 40 ]. Evidence demonstrates that the composition of microbiota impacts responses to anticancer immunotherapies and can be a novel biomarker of response assessment [ 256 , 257 ]. It was demonstrated that the presence of specific immune‐potentiating bacteria, including Akkermansia muciniphila, Faecalibacterium prausnitzii, Bifidobacterium spp ., and Bacteroides fragilis , is critical for ICI therapy.…”
Section: Gut Microbiota and Cancer Therapy Efficacymentioning
confidence: 99%